The perception of circular economy in the framework of fashion industry. Issue 2 (February 2023) - Papamichael, Iliana; Chatziparaskeva, Georgia; Voukkali, Irene; Navarro Pedreno, Jose; Jeguirim, Mejdi; Zorpas, Antonis A
Humanity's three main components are energy, food and clothing. Each of us, individually and collectively, contributes to climate change and CO2 emissions, natural resource consumption, and social attitudes and behaviour. Global fashion trends are expected to increase in value from 1.5 trillion dollars in 2020 to around 2.25 trillion dollars by 2025, indicating that the fashion demand is on the rise. Due to climate change, soil and water scarcity, and a variety of other diseases, new natural resources must be developed from plastic fibres, natural colours must replace synthetic ones, water consumption must be reduced and the 'buy-and-throw-away philosophy' must be replaced with 'buy-less-and-these-are-needed' and incorporate the 12 'R' strategies to aid the transition to a circular economy. In the context of waste management as well as on the development of new strategy approach, the fashion industry requires a new business circular model and furthermore a new mindset.